Sensible or senseless : a frame analysis of the Sensible Sentencing Trust's penal populist discourse : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Sociology at Massey University - Rimmer, Daniel (Massey University, 2011)
Recently many western societies, including New Zealand, have seen a distinct change in public attitudes towards law and order. Support for more punitive forms of punishment have seen governments adopt tougher penal and judicial policies. Scholarly attempts to define and understand this phenomenon have resulted in creation of 'penal populism'. Penal populism operates as a discourse that defines the arguments made for tougher sentences, harsher prison conditions, and greater rights for victims' of crime as well as conceptualizing the intricate social conditions from which these changes are born. This research is concerned with the discursive positions used to construct penal populist discourse; the ideas which argue for punitive reform. The aim of this research is to delineate and understand the discursive resources deployed by penal populist organizations as they seek support from the public. This research examines the penal populist discourse produced by the Sensible Sentencing Trust as a case study. The SST is New Zealand's preeminent organization dedicated to punitive reform. As a penal populist organization, the SST operate within a complex penal populist social movement; a global collectivity, where various groups and actors are bound by a punitive narrative. Frame analysis, a qualitative research method, will be used to identify penal populist discursive positions and understand their function as a resource used to elicit support from the public. The three fundamental processes of diagnostic, prognostic, and motivational framing will be identified to understand how the SST frames their discourse to produce a meaningful punitive message that resonates with the public. This research suggests that the SST gain and retain support for their cause by adapting fundamental conservative concepts with their penal populist discursive positions. The SST act as a signifying agent, interpreting the political philosophy of compassionate conservatism and aligning conservative principles. This act of re-contextualizing conservative concepts to suit the discursive needs of New Zealand's law and order debate translates their inherent resonance into the punitive narrative. Compassionate conservatism functions as a master frame, a conservative grammar, or algorithm that structures penal populist discourse making it strike a responsive chord with conservative members of the public. This act of framing however has potentially negative implications. The SST's framing creates an anti-liberalism frame that acts as an important discursive unit. This frame is hegemonic; seeking to dominate the national law and order conversation by casting contrary penal and judicial discourses as an adversary. This has the effect of divisively curtailing constructive law and order debate in New Zealand.
Keywords: Sensible Sentencing Trust; Public opinion, New Zealand; Criminal justice; Sentences (Criminal procedure); Punishment